Relationships between highly skilled golfers` clubhead velocity and force producing capabilities during vertical jumps and an isometric mid-thigh pull - Wells, J. E. T.; Mitchell, A. C. S.; Charalambous, L. H.; Fletcher, I. M. (Journal of Sports Sciences, 2018)
Whilst previous research has highlighted significant relationships between golfers` clubhead velocity (CHV) and their vertical jump height and maximum strength, these field-based protocols were unable to measure the actual vertical ground reaction force (vGRF) variables that may correlate to performance. The aim of this study was to investigate relationships between isometric mid-thigh pull (IMTP), countermovement jump (CMJ), squat jump (SJ) and drop jump (DJ) vGRF variables and CHV in highly skilled golfers. Twenty-seven male category 1 golfers performed IMTP, CMJ, SJ and DJ on a dual force platform. The vertical jumps were used to measure positive impulse during different stretch-shortening cycle velocities, with the IMTP assessing peak force (PF) and rate of force development (RFD). Clubhead velocity was measured using a TrackMan launch monitor at a golf driving range. Pearsons correlation coefficient analyses revealed significant relationships between peak CHV and CMJ positive impulse (r = 0.788, p < 0.001), SJ positive impulse (r = 0.692; p < 0.001), DJ positive impulse (r = 0.561, p < 0.01), PF (r = 0.482, p < 0.01), RFD from 0-150 ms (r = 0.343, p < 0.05) and RFD from 0-200 ms (r = 0.398, p < 0.05). The findings from this investigation indicate strong relationships between vertical ground reaction force variables and clubhead velocity.